An Ethnolinguistic Perspective on Lexicons of Traditional House in Menyali Village, North Bali - I Gede Budasi; Made Sri Satyawati (Jurnal Kajian Bali (Journal of Bali Studies), 2021)
This study aims at identifying the concepts and the lexicons of traditional Balinese houses in Menyali Village, Sawan District, Buleleng Regency. This study is a descriptive qualitative research that involved three respondents, who were selected purposively. The data were collected through interviews and observation and analyzed using an interactive data analysis model. This study found that the Menyali community views that the tri mandala concept underlines its traditional house's spatial pattern. It includes nista (the profane lying), madya (middle lying for living area), and utama (the highest and holiest lying). It is also spiritually connected to two spiritual concepts, kangin-kauh (the directional axis of sunrise and sunset) and kaje-kelod (the directional axis of mountain and sea). This study identified 24 lexicons connected to the utama mandala, 7 to the madya mandala, and 5 to the nista mandala. The lexicon number is influenced by the area function and the rituals held in those areas.